EFFECTS OF SUBSTRATES, WEIGHT AND PHYSIOLOGICAL STAGE OF SUCKERS ON MASSIVE PROPAGATION OF PLANTAIN (MUSA PARADISIACA L.) - Tchoa, Kone; André, SoumahoroBrahima; Zana, CoulibalyKpatolo; Siaka, Traore; Daouda, Kone; Mongomaké, Kone (International Journal of Research -GRANTHAALAYAH, 2016)
Plantain (Musa paradisiaca) serves as a major staple food. However, its production is seasonal and this situation led to a shortage of more than five months (June to October). The extension of cultivable areas and the use of high yielding improved varieties are severely limited by the low availability of planting materials free of diseases and parasites. The purpose of this study is to establish optimal conditions for the mass production of clean planting materials. Freshly harvested suckers from plantain namely ‘‘Corne 1’’, ‘‘Orishele’’, ‘‘French 2’’ and ‘‘Red Ebanga’’ and suckers dried and stored for one month were trimmed and peeled so as to have four weight ranges. The prepared suckers were planted in propagator filled with different substrates. The results revealed that whatever the culture substrate used, the shortest time to induce shoots and the higher number of shoots were observed with dehydrated and non-dehydrated suckers larger than 750g. Non-dehydrated Suckers with this weight expressed the longer lifetime (124-140 days). Among the substrates tested, shoots induction was faster with non-dehydrated suckers on fiber coco (12 days) and with dehydrated suckers on mix sawdust (15 days).